Effects of sowing date on vegetative growth, yield and storability of two onion (Allium cepa L.) cultivars in the River Nile State, Sudan - Ahmed Alamin, Hassan Abdelmotalib; Elkashif, Mohamed; Ali, Mohamed (Gezira Journal of Agricultural Science, 2017)
Onion is one of the most important vegetable crops in the Sudan. Sowing date and cultivars are crucial factors for onion production and storability in the River Nile State. Therefore, the objective of this study was to determine the effects of sowing date on vegetative growth, yield and storability of the two onion ( Allium cepa L.) cultivars Baftaim and Abuferwa in the River Nile State, Sudan. Experiments were carried out at Shendi Research Station farm during two consecutive seasons of 2014/15 and 2015/16. Treatments consisted of three sowing dates, which were first week of December, January and February. Treatments were arranged in a split- plot design with three replicates. Main plots were assigned to the sowing dates and sub-plots to the cultivars. Results showed that the first week of December sowing date significantly resulted in the most vigorous vegetative growth and the highest total yield in both seasons. The cultivar Baftaim had more vigorous vegetative growth, larger bulb size and higher total yield than the local cultivar Abufrewa in both seasons. However, Abufrewa cultivar had higher dry matter content and better storability than Baftaim. Early transplanting of onion in the first week of December resulted in higher postharvest losses than late transplanting in both seasons. It is recommended to transplant Baftaim cultivar in the first week of December for immediate marketing and Abufrewa in the first week of February for long term storage. يعتبر البصل من اهم محاصيل الخضر في السودان . المعاملات الفلاحية مثل تاريخ الزراعة والاصناف تعتبر من العوامل الهامة جدا في انتاج وتخزين البصل في ولاية نهر النيل. هدفت الدراسة إلي معرفة تأثير تاريخ الزراعة علي النمو الخضري والإنتاجية والقدرة التخزينية لصنفين من  البصل. أجريت هذه التجربة بالمزرعة التجريبية بمحطة بحوث شندي ، ولاية نهر النيل في الموسمين (2014/15- و015/16).اشتملت المعاملات علي ثلاثة تواريخ للزراعة وهى الاسبوع الأول من ديسمبر ويناير وفبراير مع صنفين من البصل وهى بافطيم و ابوفريوة.  استخدم تصميم القطع المنشقة بثلاث مكررات. وزعت معاملات  تاريخ الزراعة على القطع الرئيسية والاصناف على القطع الثانوية. أظهرت النتائج أن زراعة البصل في الاسبوع الأول من ديسمبر أعطت  افضل نمو خضري وأعلى إنتاجية في كلا الموسمين.  الصنف بافطيم أعطى أفضل  نمو خضري وأكبر حجم للأبصال وأعلي إنتاجيه مقارنة مع الصنف أبوفريوة في كلا الموسمين. لكن الصنف أبوفريوة أعطي أعلي نسبه من المادة الجافة و افضل قدرة تخزينية مقارنة بالصنف بافطيم. زراعة البصل مبكرا في الاسبوع الاول من ديسمبر أعطت أعلى فاقد ما بعد الحصاد بالمقارنة مع الزراعة المتأخرة في كلا الموسمين. استنادا علي هذه النتائج نوصي بزراعة الصنف بافطيم في الاسبوع الأول من ديسمبر للتسويق العاجل وزراعة الصنف ابوفريوة  في الاسبوع الاول من فبراير للتخزين طويل الامد.